Characterization of Vancomycin Resistant Enterococci and Drug Ligand Interaction between vanA of E. faecalis with the Bio-Compounds from Aegles marmelos - Jayavarsha V; Smiline Girija A.S; Shoba Gunasekaran; Vijayashree Priyadharsini J (Journal of Pharmacopuncture, 2023)
Objectives: Enterococcus faecalis is a gram positive diplococci, highly versatile and a normal commensal of the gut microbiome. Resistance to vancomycin is a serious issue in various health-care setting exhibited by vancomycin resistant Enterococci (VRE) due to the alteration in the peptidoglycan synthesis pathway. This study is thus aimed to detect the VRE from the patients with root caries from the clinical isolates of E. faecalis and to evaluate the in-silico interactions between vanA and the Aegles marmelos bio-compounds.Methods : : E. faecalis was phenotypically characterized from 20 root caries samples and the frequency of vanA and vanB genes was detected by polymerase chain reaction (PCR). Further crude methanolic extracts from the dried leaves of A. marmelos was assessed for its antimicrobial activity. This is followed by the selection of five A. marmelos bio-compounds for the computational approach towards the drug ligand interactions.Results : : 12 strains (60%) of E. faecalis was identified from the root caries samples and vanA was detected from two strains (16%). Both the stains showed the presence of vanA and none of the strains possessed vanB. Crude extract of A. marmelos showed promising antibacterial activity against the VRE strains. In-silico analysis of the A. marmelos biocompounds revealed Imperatonin as the best compound with high docking energy (–8.11) and hydrogen bonds with < 140 TPSA (Topological polar surface area) and zero violations.Conclusion : : The present study records the VRE strains among the root caries with imperatorin from A. marmelos as a promising drug candidate. However the study requires further experimentation and validation.